Towards the financial well-being of Gen-Z: A study at Tri Ratna School – Jakarta with Locus of Control as a mediation variable - Liny, Liny; Purnama, Eka Desy (Global Academy of Business Studies, 2024)
Purpose: This study aimed to analyze the influence of financial literacy and lifestyle on financial well-being among Generation Z (Gen-Z), with the locus of control as a mediating variable. In this study, the locus of control refers to an individual's belief in internal and external influences in decision-making or taking action, which is expected to mediate the relationship between financial literacy, lifestyle, and financial well-being. Research methodology: The data used in this study were collected through a survey of Gen-Z students, teachers, and staff members at Tri Ratna School-Jakarta, aged between 16 and 27 years. The analysis was conducted using Partial least squares structural equation modeling (PLS-SEM) was used to test the relationships between variables. Results: This study’s findings are expected to provide insights into the importance of financial literacy and the influence of lifestyle in shaping the financial well-being of Gen Z, as well as the role of locus of control in strengthening or weakening these influences. The findings are expected to serve as a reference for financial education and the development of more effective policies to improve the financial well-being of younger generations in Indonesia, particularly at Tri Ratna School-Jakarta. Conclusions: Financial well-being among Gen-Z is determined not only by literacy and lifestyle but also by the locus of control, which functions as a psychological driver of effective financial behavior. Integrating financial education with self-control and lifestyle management can improve financial resilience. Limitations: This study was limited to one institution in Jakarta, which may not represent a broader population. It also relies on self-reported data that may be biased. Contribution: This research contributes to financial education by highlighting the importance of the locus of control and lifestyle choices in shaping Gen’s financial well-being, providing insights for schools and policymakers.